Analysis of Community Participation-Based Agrotourism Development in Sigerongan Village West Lombok Regency - Sugiarta Sugiarta; Budy Wiryono; Siti Zainab (Journal of Biology, Environment, and Edu-Tourism, 2025)
Agrotourism has the potential to boost rural economies while preserving local culture and natural resources. This research seeks to evaluate the role of the local community in advancing agrotourism development in Sigerongan Village, West Lombok Regency, and aims to design a development model that emphasizes community participation. The findings are intended to serve as a valuable resource for government policymakers to better engage local communities in agrotourism projects and to provide a reference for subsequent studies. Employing a descriptive methodology, the study utilizes qualitative analytical methods. Data collection involved primary and secondary sources gathered through observation, detailed interviews, and literature review.A total of 33 respondents were selected, three from each hamlet. Results show low community participation in planning and supervision stages, while participation in implementation is more evident—such as providing halfway houses for tourists. Most residents are farmers working in groups near tourist areas, hoping that tourists not only enjoy the natural attractions but also engage in activities like harvesting or catching local produce. The community aspires for Sigerongan Village to be known for its unique agrotourism brand, focusing on rice (Oryza sativa), cassava (Manihot esculenta), mango (Mangifera indica), guava (Psidium guajava), mangosteen (Garcinia mangostana), rambutan (Nephelium lappaceum), and fisheries.